Framing Analysis Using Zhongdang Pan and Gerald M. Kosicki’s Model In Androgyny News Coverage On Wolipop.Detik.Com - Mulia Rachman; Fakhrur Rozi (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyse how Wolipop.detik.com frames androgyny in fashion and lifestyle news. This study departs from the view that androgyny in the media sphere does not appear neutrally, but is constructed through language choices, narrative arrangement, visual emphasis, and specific meaning-making processes that influence how the public understands gender expression that differs from common norms. This study uses a descriptive qualitative approach with Zhongdang Pan and Gerald M. Kosicki’s framing analysis model, which consists of syntactic, script, thematic, and rhetorical structures. This framework is strengthened by Judith Butler’s theory of gender performativity to examine how masculine and feminine expressions in the media are produced through the repeated presentation of bodies, clothing, style, and visual appearance. The primary data consist of Wolipop news texts containing representations of androgyny, while the secondary data are drawn from books, scholarly journals, academic articles, and relevant previous studies. The findings show that Wolipop dominantly frames androgyny as a visual expression that is aesthetic, modern, inspirational, and closely associated with popular culture. The dominant patterns that emerge are the androgyny aestheticisation frame, celebrity legitimation frame, and lifestyle-oriented frame, which position androgyny as a fashion and lifestyle trend rather than as an issue of gender identity debated within a broader social dimension. These findings extend media and gender studies by showing that digital lifestyle media do not merely present fluid gender expression as a visual trend, but also construct symbolic legitimacy for androgyny through aesthetic, popular, and depoliticised framing mechanisms.